Implementasi Global Citizenship Education (GCED) sebagai Pendekatan Edukatif Isu Sampah di Desa Karanganyar - Abdullah, Abdullah; Mahendra, Yustika Citra; Purba, Dano; Rozuli, Ahmad Imron; Yunas, Novy Setia; Febrianika, Alyavera; Aulia, Alfina Putri; Chandra Wijaya, Sung Sang; Aufa, Neyla Marshadina; Fauzi, Achmad (Lembaga Dongan Dosen, 2025)
Karanganyar Village, Poncokusumo District, Malang Regency, is an agricultural area with great potential in horticulture and plantations. However, the main challenge faced by this village is the lack of integration in the management of household waste and the agricultural sector. The lack of public awareness regarding waste separation and utilization further worsens the environmental situation. In addition, the economic potential of local UMKM has not been fully utilized due to a lack of innovation, marketing, and training. This study aims to implement a Global Citizenship Education (GCED) approach in village education to increase environmental awareness and entrepreneurial skills among the community. The methods applied are participatory through counseling, waste management training, and awareness campaigns based on global education. The findings show that the GCED method can increase community knowledge about waste management and encourage the formation of environment-based business groups. These activities also encourage participatory enthusiasm in maintaining cleanliness and supporting the circular economy in villages. In conclusion, the implementation of GCED in village education can be an effective method for sustainable waste management and strengthening the local economy.